Determination of Practice Course Experiences of Nursing First Class Students in the Pandemic Process - Kübra Berber; Özlem Albayrak (Güncel Hemşirelik Araştırmaları Dergisi)
Objective: This study was planned to determine the experiences and problems experienced in terms of skill acquisition within the scope of nursing education of first-year nursing students who conduct distance and asynchronous practice courses in clinical, laboratory and simulation applications, which are an indispensable part of nursing education.Method: This descriptive study was conducted with first-year students attending a nursing basics course and continuous active education in the spring semester of the 2019-2020 academic year in a Health School. 88 students who voluntarily agreed to participate in the study were included. Data were collected using an online form consisting of introductory information created by the researchers and questions about student experiences. Statistical analysis of the study was performed using frequency, percentage, arithmetic mean and standard deviation tests in the SPSS program.Results: While 20.5% of the students stated that they had difficulty administering parenteral drugs within the scope of skill practices, 68.2% of them stated that they experienced stress while applying. 75% of the students participating in the research stated that distance education was not sufficient for the vocational practice course and 81.8% stated that they were not ready for the clinical environment after distance education.Usage in Practice: The pandemic has suddenly placed distance education in our lives. The results of our study will guide the practices in terms of developing new strategies in nursing education suitable for future scenarios.